2012
DOI: 10.1002/humu.22177
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Expansion in Mouse and Human Carriers of Fragile X Premutation Alleles

Abstract: Repeat Expansion Diseases result from expansion of a specific tandem repeat. The three Fragile X-related disorders (FXDs) arise from germline expansions of a CGG•CCG repeat tract in the 5′ UTR of the FMR1 gene. We show here that in addition to germline expansion, expansion also occurs in the somatic cells of both mice and humans carriers of premutation alleles. Expansion in mice primarily affects brain, testis and liver with very little expansion in heart or blood. Our data would be consistent with a simple tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(135 citation statements)
references
References 61 publications
7
128
0
Order By: Relevance
“…However, our analysis indicates an unmethylated expansion of approximately 160 repeats. The discrepancy in PM allele size between our study and the published literature could be due to a passageinduced instability and expansion in our cell line clone which is in agreement with a recent report on the same PM male cell line [31].…”
Section: Fmr1 Genotypes In Ccr Samplessupporting
confidence: 91%
“…However, our analysis indicates an unmethylated expansion of approximately 160 repeats. The discrepancy in PM allele size between our study and the published literature could be due to a passageinduced instability and expansion in our cell line clone which is in agreement with a recent report on the same PM male cell line [31].…”
Section: Fmr1 Genotypes In Ccr Samplessupporting
confidence: 91%
“…For example, in human HD patients, dramatic expansions (gains of up to 1000 repeats) are observed in striatal cells, the brain region most affected by the disease (Kennedy et al ., 2003). Many mouse models also show extensive repeat expansion in the brain (for example, Libby et al ., 2003; Lokanga et al ., 2013; Mangiarini et al ., 1997) and specifically in post-mitotic neurons (Gonitel et al ., 2008). Since even expansion-prone somatic cells that are not post-mitotic proliferate very slowly, non-replicative expansion mechanisms are likely to explain many somatic expansions.…”
Section: Repeat Expansions Cause Human Diseasementioning
confidence: 99%
“…For example, pluripotent stem cells from individuals with FRDA and DM1 show expansion while the fibroblasts from which they are derived do not (Du et al ., 2012, 2013). In mouse models of the TNR diseases, some tissues are more expansion prone than others and these differ between different disease models (Clark et al ., 2007; Fortune et al ., 2000; Goula et al ., 2009; Kennedy et al ., 2003; Lokanga et al ., 2013), suggesting that a combination of cell-type-specific factors and locus-specific factors must play a role in the determination of expansion frequency.…”
Section: Repeat Expansions Cause Human Diseasementioning
confidence: 99%
“…The CGG repeats within the FMR1 gene predispose it to instability and the occurrence of size mosaicism, in which individuals present with different CGG repeat allele sizes such that some cells carry a full mutation allele while others carry a premutation allele; a situation that is common among individuals with FXS (Loesch et al, 2004; Lokanga et al, 2013). Notably, Nolin et al (1994) analyzed a group of affected males with FXS by Southern Blotting and found 41% to be size mosaic.…”
Section: Introductionmentioning
confidence: 99%